2014
DOI: 10.1001/jamaophthalmol.2014.1019
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Visual Acuity Loss in the Comparison of Age-Related Macular Degeneration Treatments Trials

Abstract: Although anti-vascular endothelial growth factor treatment of neovascular age-related macular degeneration (AMD) results in improved vision overall, loss of substantial vision can occur. Understanding the processes that lead to loss of vision may lead to preventive strategies.OBJECTIVE To determine the incidence, characteristics, causes, and baseline predictors of sustained visual acuity loss after 2 years of treatment with ranibizumab or bevacizumab for neovascular AMD. DESIGN, SETTING, AND PARTICIPANTS A coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
64
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 15 publications
5
64
0
1
Order By: Relevance
“…26 Also some of the baseline characteristics were found to be associated with sustained VA loss, which were presence of non-foveal geographic atrophy, larger CNV area, poor baseline VA, o20/50 baseline VA in the fellow eye, and intraretinal fluid not at the foveal center. 26 The patients' clinical characteristics, lesion type, and misdiagnosis have been evaluated thoroughly and constitute now the main discussed topics in anti-VEGF nonresponse literature. 15,16,26 Factors affecting drug pharmacodynamics and pharmacokinetics such as receptor downregulation, autoantibody formation, change in drug distribution, and absorption have also been shown to be related to nonresponse.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…26 Also some of the baseline characteristics were found to be associated with sustained VA loss, which were presence of non-foveal geographic atrophy, larger CNV area, poor baseline VA, o20/50 baseline VA in the fellow eye, and intraretinal fluid not at the foveal center. 26 The patients' clinical characteristics, lesion type, and misdiagnosis have been evaluated thoroughly and constitute now the main discussed topics in anti-VEGF nonresponse literature. 15,16,26 Factors affecting drug pharmacodynamics and pharmacokinetics such as receptor downregulation, autoantibody formation, change in drug distribution, and absorption have also been shown to be related to nonresponse.…”
Section: Discussionmentioning
confidence: 96%
“…15 In the pivotal multicenter studies,~5% of the patients were found to be unresponsive to anti-VEGF treatment, and showed sustained VA loss despite treatment; these patients have been called as nonresponders. 11,13,14,26 The sustained VA loss has been attributed to several factors, such as fibrous scar formation, pigmentary anomalies, geographic atrophy, RPE tear, retinal thinning, and thickening. 26 Also some of the baseline characteristics were found to be associated with sustained VA loss, which were presence of non-foveal geographic atrophy, larger CNV area, poor baseline VA, o20/50 baseline VA in the fellow eye, and intraretinal fluid not at the foveal center.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations